ANALYSIS OF FACTORS AFFECTING ADOLESCENT SEXUAL BEHAVIOR IN SIDOARJO: A HOLISTIC APPROACH - Rosyidah, Rafhani; Nurul Azizah (International Journal Multidisciplinary (IJMI), 2024)
Adolescent sexual behavior is a significant concern in efforts to maintain reproductive and mental health among adolescents in Indonesia. This study aims to analyze the factors influencing adolescent sexual behavior in Sidoarjo Regency. Using a holistic approach, this research examines the impact of various internal factors such as reproductive health knowledge and self-control, as well as external factors such as peer influence, family, and social media exposure. This study employs a descriptive quantitative method with a survey approach, involving 300 adolescents from several high schools in Sidoarjo. The results indicate that peer influence and social media exposure significantly contribute to adolescent sexual behavior, followed by low reproductive health knowledge. Based on these findings, an integrated intervention program involving the active role of families, schools, and media is needed to improve adolescents’ understanding and self-control.